Transcriptomic profiling and differential analysis revealed the neurodevelopmental toxicity mechanisms of zebrafish (Danio rerio) larvae in response to tetrabromobisphenol A bis(2–hydroxyethyl) ether (TBBPA-DHEE) exposure - Okeke, Emmanuel Sunday; Luo, Mengna; Feng, Weiwei; Zhang, Yiran; Mao, Guanghua; Chen, Yao; Zeng, Zhengjia; Qian, Xian; Sun, Lei; Yang, Liuqing; Wu, Xiangyang (Comparative biochemistry and physiology. Toxicology & pharmacology, 2022)
Tetrabromobisphenol A bis(2-hydroxyetyl) ether (TBBPA-DHEE) is among the main derivatives of Tetrabromobisphenol A (TBBPA). Result from previous study showed that TBBPA-DHEE can cause neurotoxicity in rat. In this study, zebrafish larvae were used for evaluation of TBBPA-DHEE-induced developmental toxicity, apoptosis, oxidative stress and the potential molecular mechanisms of action. Our result showed that TBBPA-DHEE exposure caused a significant concentration-dependent developmental toxicity endpoints like death rate, malformation rate, growth rate. TBBPA-DHEE altered locomotor and enzymes activities of larvae and caused apoptosis within the brain indicating the potential TBBPA-DHEE-induced cardiac, brain impairment in the zebrafish larvae. Our transcriptomic analysis shows that 691 genes were differentially expressed (DEGs) (539 upregulated, 152 downregulated). The KEGG and GO enrichment pathway analysis shows that the DEGs were involved in development, immunity, enzyme activity. Our study provides novel evidence on the neurodevelopmental toxicity and toxicity mechanism of TBBPA-DHEE which are vital for assessment of the environmental toxicity and risk assessment of the chemical. [Display omitted] •TBBPA-DHEE is triggered the induction of apoptosis.•TBBPA-DHEE altered the locomotor activities of the larvae.•TBBPA-DHEE caused increase in mortality and malformation rate in zebrafish larva.•Antioxidant enzyme activities were adversely affected by TBBPA-DHEE exposure.•TBBPA-DHEE altered the expression level of mmp9, casp3b, il1b, fosab etc.